2022
DOI: 10.4103/ijo.ijo_2513_21
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience in treating polypoidal choroidal vasculopathy with brolucizumab in Indian eyes – A multicenter retrospective study

Abstract: Purpose: To report the initial experience of managing treatment-resistant and treatment-naïve eyes with polypoidal choroidal vasculopathy (PCV) by using brolucizumab 6 mg. Methods: This was a retrospective multicentric series of all consecutive eyes with PCV treated with brolucizumab. Treatment resistance was defined as taking at least six prior anti-VEGF injections over the past 1 year and showing persistent disease activity in the form of intra (IRF) or subretinal flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Three papers with four subgroups reported change of treatment intervals: Ueda-Consolve et al reported an increase from 7.4 ± 1.4 weeks to 11.6 ± 2.6 weeks after the switch in 19 eyes with type 1 macular neovascularization and from 6.9 ± 1.3 weeks to 11.7 ± 3.1 weeks after the switch in 23 eyes with polypoidal choroidal vasculopathy after 18 months [ 21 ]. Giunta et al showed an increase from 4.7 ± 2.3 weeks to 6.8 ± 2.8 weeks in a cohort of 73 patients at least three months after the switch to brolucizumab [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three papers with four subgroups reported change of treatment intervals: Ueda-Consolve et al reported an increase from 7.4 ± 1.4 weeks to 11.6 ± 2.6 weeks after the switch in 19 eyes with type 1 macular neovascularization and from 6.9 ± 1.3 weeks to 11.7 ± 3.1 weeks after the switch in 23 eyes with polypoidal choroidal vasculopathy after 18 months [ 21 ]. Giunta et al showed an increase from 4.7 ± 2.3 weeks to 6.8 ± 2.8 weeks in a cohort of 73 patients at least three months after the switch to brolucizumab [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Important points and outcomes from real-world data are outlined in Table 1. 28,29,[38][39][40][41][42][43][44] The readers are encouraged to access individual studies for details of methodology and results.…”
Section: Real-world Datamentioning
confidence: 99%
“…has shown promising initial results of pro re nata Brolucizumab therapy in recalcitrant PCV eyes in Indian settings. [ 9 ] It helped in reducing subretinal/intraretinal fluid, PED height and in maintaining visual acuity gains. HAWK Phase III trial subanalysis also reported that visual outcomes achieved with brolucizumab q12w/q8w treatment over 96 weeks were comparable with aflibercept treatment on a fixed q8w dosing.…”
mentioning
confidence: 99%
“…In the study conducted by Chakraborty et al , no such events were found. [ 9 ] This could be due to the differential racial response and pro re nata dosing regimen usage which might have reduced the antigenic load caused due to frequent repeated injections. Novartis has also communicated that Brolucizumab should not be administered at intervals of less than 2 months after three monthly loading doses.…”
mentioning
confidence: 99%